Proceedings of the 2000 ACM Symposium on Applied Computing - Volume 1 2000
DOI: 10.1145/335603.335629
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing human gait patterns for malfunction detection

Abstract: Clinical gait analysis is an area aiming at the provision of support for diagnoses and therapy considerations, the development of bio-feedback systems, and the recognition of effects of multiple diseases and still active compensation patterns during the healing process. The data recorded with ground reaction force measurement platforms is a convenient starting point for gait analysis. We discuss the usage of raw data from such force platforms for gait analysis and show how supervised artificial neural networks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…However, disappointing results led to further investigation. Kohle and Merkl [5] suggested that the number of degrees of freedom is a direct cause of the variability in walking and therefore, unrestricted natural walking is likely to show the most variable profile in contrast to someone with a walking disorder. Given that affected gait is usually down to a limitation in limb movement, be it from muscular or nervous defects, it was justifiable to classify just these limited movements, rather than the many classes of 'natural' walking.…”
Section: Distance Calculationmentioning
confidence: 99%
“…However, disappointing results led to further investigation. Kohle and Merkl [5] suggested that the number of degrees of freedom is a direct cause of the variability in walking and therefore, unrestricted natural walking is likely to show the most variable profile in contrast to someone with a walking disorder. Given that affected gait is usually down to a limitation in limb movement, be it from muscular or nervous defects, it was justifiable to classify just these limited movements, rather than the many classes of 'natural' walking.…”
Section: Distance Calculationmentioning
confidence: 99%
“…The lowfrequency (below 500 Hz) responses are well known from the previous investigations. [1][2][3][4][5][6] The vibration signal above 500 Hz (Figs. 2(a) and 2(b)) has a broadband frequency spectrum up to 22 kHz with high-frequency magnitudes comparable with the maxima of magnitudes at the low frequencies.…”
Section: Footsteps Vibration and Sound Signatures In A Buildingmentioning
confidence: 99%
“…This force is due to two components: the normal force and the force tangential to the surface. 6 The normal force component generates the low-frequency vibrations (typically below 500 Hz) that are currently used for intruder detection by seismic methods. 5 The tangential force is governed by the horizontal motion and is equal to the force of the ground/floor reaction, or friction force.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional such research is conducted using dynamic electromyography, force platforms and joint kinematics and kinetics. [4], [5], [9] In our study, we perform a computing project based on the tri-axial accelerometers that capture human movement patterns from various body locations. The goal ofthis study is to classifying different age groups based on this movement information.…”
Section: Introductionmentioning
confidence: 99%
“…Kohle and Merkl [4] classified a number of pathological gait patterns by using the unsupervised learning strategy of self-organizing maps (SOM). Yun, Woo and Ryu [9] used a neural network that was trained using the feedback from the photo interrupter sensors that were uniformly arrange in each floor tiles.…”
Section: Introductionmentioning
confidence: 99%